1998
DOI: 10.1016/s0735-1097(98)00296-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation of cardiomyocyte hypertrophy and myocardial fibrosis over 6 years after cardiac transplantation

Abstract: Cardiomyocyte diameter of the transplanted heart gradually increases over time, while percent myocardial fibrosis rises early and remains in a modestly elevated plateau after 2 months posttransplant. These histostructural changes likely contribute to the hemodynamic and cardiac functional alterations commonly observed posttransplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 14 publications
5
65
1
4
Order By: Relevance
“…Interstitial ET-1 was associated with a lower cellular rejection score, suggesting a dissociation between rejection and fibrosis, as has been shown in pediatric liver transplants. 14 The concept of fibrosis after transplantation has been thoroughly examined by Armstrong and his colleagues, 15 who evaluated serial endomyocardial biopsies on 50 cardiac transplant patients followed over 5 years. The investigators showed that myocardial fibrosis develops early and remains modestly elevated 2 months after transplant, indicating that peri-transplant factors might be responsible for this fibrotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial ET-1 was associated with a lower cellular rejection score, suggesting a dissociation between rejection and fibrosis, as has been shown in pediatric liver transplants. 14 The concept of fibrosis after transplantation has been thoroughly examined by Armstrong and his colleagues, 15 who evaluated serial endomyocardial biopsies on 50 cardiac transplant patients followed over 5 years. The investigators showed that myocardial fibrosis develops early and remains modestly elevated 2 months after transplant, indicating that peri-transplant factors might be responsible for this fibrotic process.…”
Section: Discussionmentioning
confidence: 99%
“…After counterstaining with Harris hematoxylin (Sigma  ) for 25 seconds, the slides were mounted and analyzed by light microscopy. Photomicrographs were analyzed by LGMC-image software version 1.0 and the fractional percentages of the immunoreactive area to aorta and myocardium CD40L were acquired (Armstrong et al, 1998).…”
Section: Histological and Immunohistochemical Proceduresmentioning
confidence: 99%
“…All of these aspects may also play an important role in post-heart transplant patients being frequently influenced by risk factors of diastolic dysfunction such as hypertension, diabetes mellitus, obesity, and metabolic syndrome [11][12][13][14][15][16] . As demonstrated previously 11 and confirmed in this study, systemic hypertension is a very common finding in patients after heart transplantation.…”
Section: Aspects Of Left Ventricular Filling Pressure Elevation and Dmentioning
confidence: 99%